Implementasi Sistem Informasi Data Barang Masuk Keluar Pada Perancanaan Perusahaan La Maison - Arief Rahman Hakim (PT. ALHAFI BERKAH INDONESIA, 2023)
Information System for Recording Incoming and Outgoing Goods (case study at La Maison), is an information system that can help companies input incoming and outgoing goods from the warehouse at La Maison. The work on this system uses the Agile method where work is carried out sequentially in a linear manner. The process of recording incoming and outgoing goods, which is done by filling in the inventory form and then transferring it to Microsoft Excel, can be increased in efficiency by developing a web-based information system. So that problems such as searching for data that takes longer and incorrectly inputting the number of item data can be avoided. The results of this research are an application that can help companies input incoming goods and outgoing goods from the warehouse.